1988
DOI: 10.1037/0096-1523.14.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Visual selection from multielement displays: Measuring and modeling effects of exposure duration.

Abstract: In a partial-report experiment, subjects reported the digits from a circular array of digits and letters terminated by a pattern mask. Individual frequency distributions of the number of correctly reported digits were analyzed as functions of number of digits (2, 4, or 6) and number of letters (0, 2, 4, 6, or 8) at nine exposure durations ranging from 10 to 200 ms. The distributions (hundreds of data points per subject) were accurately predicted by a four-parameter fixed-capacity independent race model that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
287
1
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(310 citation statements)
references
References 18 publications
21
287
1
1
Order By: Relevance
“…A second issue concerns the role of capacity limitations in the dimension-sampling process. Evidence from visual-search and partial-report tasks suggests that the storage capacity of visual short-term memory can be limited to as little as four or five elements (e.g., Bundesen, 1987Bundesen, , 1990Bundesen, Pedersen, & Larsen, 1984;Shibuya & Bundesen, 1988). As long as the number of stimulus dimensions remains within these limits, the EGCM-RT will perform as well as a limited-capacity model.…”
Section: Resultsmentioning
confidence: 99%
“…A second issue concerns the role of capacity limitations in the dimension-sampling process. Evidence from visual-search and partial-report tasks suggests that the storage capacity of visual short-term memory can be limited to as little as four or five elements (e.g., Bundesen, 1987Bundesen, , 1990Bundesen, Pedersen, & Larsen, 1984;Shibuya & Bundesen, 1988). As long as the number of stimulus dimensions remains within these limits, the EGCM-RT will perform as well as a limited-capacity model.…”
Section: Resultsmentioning
confidence: 99%
“…According to TVA, when a target is presented alone in location i, performance P i is closely approximated by an exponential function (Shibuya and Bundesen, 1988;Bundesen, 1998):…”
Section: Methodsmentioning
confidence: 99%
“…TVA analyses of partial (i.e., selective) report have previously proved useful to study normal performance (Shibuya and Bundesen, 1988;Shibuya, 1993) and to investigate deficits in pa- tients with extensive brain damage (Duncan et al, 1999;Peers et al, 2005). Duncan et al (1999) found some lowering of sensory effectiveness (A i ) and of overall weighting (w i ) regardless of target/nontarget status for the left hemifield in patients with extensive damage over the right parietal/perisylvian regions.…”
Section: Effects Of Rtms Versus Those Of Large Brain Lesionsmentioning
confidence: 99%
“…After all, if it were true that consolidation is interrupted by a mask and that the consolidation of a single letter takes only 25 ms, then this would entail that a variety of theories of the attentional blink are incorrect in assuming that this effect reflects the time course of WMC. 1 Conversely, if it were true that WMC can continue for several hundred milliseconds after a mask, then this would entail that researchers can no longer assume that backward masking can be used as a means to assess or restrict the duration of consolidation, as has been done in many previous empirical and theoretical studies (e.g., Bays et al, 2011;Bundesen, 1990;Fuller et al, 2005;Gegenfurtner & Sperling, 1993;Saults & Cowan, 2007;Shibuya & Bundesen, 1988;Sun et al, 2011;Todd et al, 2011;Vogel et al, 2006;Woodman & Vogel, 2005;Wutz & Melcher, 2013;Zhang & Luck, 2008). 2 The goal of the current study was to adjudicate between the opposing perspectives on the dynamics of WMC.…”
Section: The Present Studymentioning
confidence: 99%